Dores musculares cervicais e DTMs: revisão de literatura - Kawano, Juliana Sayuri [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
Lots of people suffers with musculoskeletal problems in the back and orofacial region. Currently, the presence of these changes has received attention from researchers as it is a reason for seeking health treatments as well as with the decrease in quality of life. Changes in cervical muscles and posture affect most individuals and appear to be responsible for making the treatments for more complex pain. Among the problems that generate orofacial pain, are present Temporomandibular Disorders (TMD) are characterized by a number of signs and symptoms such as pain, joint sounds, dysfunction and limitation in jaw movements. These disorders can affect the temporomandibular joints (TMJ) and masticatory muscles, and they affect the muscles, may represent local changes or even be characterized by pain. In these cases, the location of pain in the cervical and masticatory muscles appears to be important for the diagnosis and treatment of the source of pain, since they must be directed to two regions. Furthermore, postural changes of the head and its relationship with TMD has also been the subject of great scientific debates, without, however, be confirmed correlations between them. Hence, the objective of this work was to present a review of literature on cervical and TMD pain. It was noted that there are studies that seek to evaluate the cause and effect of the presence of pain and some cervical changes with the presence of TMD, especially pain in the masticatory muscles, with inconclusive results. The presence of trigger points in the cervical muscles and their relationship to pain in the masticatory muscles seems to be sedimented without however having clarified the pathophysiological mechanisms. Regarding the presence of postural changes and their relationship with TMD, many controversies remain to be investigated

Grande parte da população sofre com problemas músculo esqueléticos na região das costas e orofacial. Atualmente, a presença destas alterações tem recebido atenção dos pesquisadores, pois é motivo de busca por tratamentos de saúde, bem como por grande diminuição na qualidade de vida da população. Alterações na musculatura cervical e postura afetam grande parte dos indivíduos e parecem ser responsáveis por tornarem os tratamentos para a dor mais complexos. Dentre os problemas que geram dor orofacial, estão presentes as Disfunções Temporomandibulares (DTMs) que são caracterizadas por uma série de sinais e sintomas como dor, ruídos articulares, disfunção e limitação nos movimentos mandibulares. Estas disfunções podem afetar as articulações temporomandibulares (ATMs) e os músculos da mastigação, sendo que quando afetam os músculos, podem representar alterações locais ou ainda, serem caracterizadas por dor referida. Nestes casos, a localização da dor nos músculos cervicais e mastigatórios parece ser importante para o diagnóstico e o tratamento da fonte de dor referida, uma vez que eles devem ser direcionados às duas regiões. Além disto, alterações posturais da cabeça e sua relação com as DTMs também têm sido objeto de grandes debates científicos, sem, contudo, serem confirmadas correlações entre elas. Diante disto, o objetivo deste trabalho foi apresentar uma revisão de literatura sobre as dores cervicais e as DTMs através de pesquisa em bases de dados. Foi observado que existem estudos que buscam avaliar a relação causa e efeito da presença de dor e algumas alterações cervicais com a presença de DTMs, principalmente a dor nos músculos mastigatórios, com resultados ainda inconclusivos. A presença de pontos de gatilho nos músculos cervicais e sua relação com dores...
Keywords: Mialgia; Músculos mastigatórios; Síndrome da disfunção da articulação temporomandibular; Masticatory muscles